HUBUNGAN ANTARA HARGA SAHAM DAN KEBIJAKAN DIVIDEN SERTA UKURAN PERUSAHAAN - I Kadek, Bagiana (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
Fluctuating stock price movements occur due to several factors, one of which is corporate action in distributing dividends. Dividends are not only a source of income for investors but are also a signal of the performance of large companies, one of which is in the manufacturing sector. The good performance of manufacturing companies is not only seen from the management of assets, it is also seen from the company's ability to pay dividends and invest in other companies, so that it can lead to an increase in the company's stock price. There are several important factors that companies consider in designing their dividend policy, one of which is company size. Firm size reflects the size of a company based on the total assets owned. This study aims to re-examine and confirm the effect of firm size on stock prices with dividend policy as a mediating variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2020. The sample determination uses a non-probability method with purposive sampling technique and obtained as many as 72 companies. The analysis technique used is path analysis. Analysis of the data in this study using the SmartPLS software version 3.3.7. The results of this study indicate that firm size has no effect on dividend policy, firm size has a positive effect on stock prices, dividend policy has a positive effect on stock prices, dividend policy is not able to mediate the effect of firm size on stock prices.